Efisiensi Dan Efektivitas Dalam Penghimpunan Dan Penyaluran Pada Program ZIS Di Laz Washal Medan - Maha, Nurita; Aisyah, Siti (JURNAL EKONOMI, MANAJEMEN, BISNIS, DAN SOSIAL (EMBISS), 2022)
The purpose of this research was to provide information regarding efficiency and effectiveness in the collection and distribution of ZIS funds at LAZ WASHAL Beramal North Sumatra. This research is descriptive qualitative research using survey and interview methods. The results of this study indicate that the efficiency and effectiveness in collecting and distributing ZIS funds have been very good and have increased quite a bit from the previous year. The proceeds from the ZIS fundraising were channeled through the ZISWAF program provided by LAZ WASHAL Charity, namely free meals (MAGER), MSME empowerment, shop repairs, 1000 Packages program for orphans, and educational scholarships